2009
DOI: 10.1142/s1088424609000279
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new glycoporphyrin derivatives through carbohydrate-substituted α-diazoacetates

Abstract: The reaction of carbohydrate-substituted α-diazoacetates with meso-tetrakis(pentafluorophenyl)porphyrinatozin(II) allows the synthesis of new glyco-hydroporphyrin derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…245 The major products of these reactions are chlorins, which, when acidified, afford the corresponding free bases with deprotected sugar units (Figure 31). These chlorin derivatives are reported to be better singlet oxygen producers than methylene blue (MB).…”
Section: Glycosylated Chlorins Isobacteriochlorins and Bacteriocmentioning
confidence: 99%
See 1 more Smart Citation
“…245 The major products of these reactions are chlorins, which, when acidified, afford the corresponding free bases with deprotected sugar units (Figure 31). These chlorin derivatives are reported to be better singlet oxygen producers than methylene blue (MB).…”
Section: Glycosylated Chlorins Isobacteriochlorins and Bacteriocmentioning
confidence: 99%
“…Cavaleiro and co-workers 245 made chlorins by reactions of meso -tetrakis(pentafluorophenyl) porphyrinatozinc(II) with α -diazoacetates derived from diacetonides of the glucofuranose (a), monoacetonide of xylofuranose (b), fructopyranose (c), and galactopyranose (d).…”
Section: Figurementioning
confidence: 99%
“…Subsequent work a generation later employed ZnF 20 TPP , the zinc chelate of H 2 F 20 TPP , in similar chemistry (Scheme ). The products upon carbene insertion encompassed the cyclopropane-fused chlorin isomers (putative 12-Zn5a−d , 12-Zn6a−d ), the bacteriochlorins, and isobacteriochlorins, although all species were not isolated for each carbene precursor ( 12-Zn5a−d and 12-Zn6b were isolated). The novelty of the carbene precursors was the ability to install an acetonide-protected glycosyl unit on the cyclopropyl ring that is integral to the pyrroline motif.…”
Section: (Cyclo)additions To Porphyrins Without Vinyl Groupsmentioning
confidence: 99%
“…TFA affording 540a-d. Singlet oxygen production studies showed the chlorins 540a-d to be better than the well-known singlet oxygen producer methylene blue with compound 540b providing the best production. No significant difference in Log P was observed, but chlorins 540a and 540c were only slightly more hydrophilic than 540b,d [271] . Similar methods were used by Hirohara et al to study a range of O-glycosylated tetraarylporphyrins and -chlorins, which showed several advantages including reduced dark cytotoxicity, improved water-solubility, better cellular uptake, and sugar-dependent photocytotoxicity [165,261,262,272,273] .…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 78%
“…All glycosylated chlorins and bacteriochlorins isopropylidene acetals could be deprotected in quantitative yields. Subsequently, this work was extended to azomethine ylides and diazoacetates [271] . A new method for the synthesis of the glyco-conjugates (536-539) was developed using CuCl to catalyze the cyclopropanation reactions of {5,10,15,20-tetra(pentafluorophenyl)porphyrinato}zinc(II) (534) with α-diazoacetates (535a-d) of glucofuranose, fructopyranose, galactopyranose and xylofuranose (Scheme 27).…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 99%